Review of Remission and Assimilation in the Correctional System with the Foundation of Human Rights - Syawal Amry Siregar; Gomgom TP Siregar; Muhammad Ansori Lubis (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research is related to the granting of remission and parole rights on the basis of the value of justice in accordance with human rights. This research was conducted to find out about the embodiment of justice in the granting of remissions and parole to convicts. Both criminals and corruption convicts. This research will also review the arrangements regarding the granting of such remissions and also the ideal concepts regarding the granting of such remissions and parole. This research will use empirical normative legal research methods that emphasize philosophical, dogmatic and conceptual sides. The data collected in this study was carried out by means of literature and document studies. Data analysis used a qualitative descriptive method. This research presents that the embodiment of justice in granting parole and release to prisoners is not entirely fair and equitable. The regulatory process regarding granting remissions and conditional release should be in accordance with the norms and not contradictory. The concept of granting remissions and parole must be balanced in terms of justice and also balanced in coaching.